Minimalist Running Shoes and Injury Risk Among United States Army Soldiers. (June 2016) - Grier, Tyson; Canham-Chervak, Michelle; Bushman, Timothy; Anderson, Morgan; North, William; Jones, Bruce H.
Background: Minimalist running shoes (MRS) are lightweight, are extremely flexible, and have little to no cushioning. It has been thought that MRS will enhance running performance and decrease injury risk. Purpose: To compare physical characteristics, fitness performance, and injury risks associated with soldiers wearing MRS and those wearing traditional running shoes (TRS). Study Design: Case series; Level of evidence, 4. Methods: Participants were men in a United States Army brigade (N = 1332). Physical characteristics and Army Physical Fitness Test data were obtained by survey. Fitness performance testing was administered at the brigade, and the types of footwear worn were identified by visual inspection. Shoe types were categorized into 2 groups: TRS (stability, cushioning, and motion control) and MRS. Injuries from the previous 12 months were obtained from the Defense Medical Surveillance System. A t test was used to determine mean differences between personal characteristics, training, and fitness performance metrics by shoe type. Hazard ratios and 95% CIs were calculated to determine injury risk by shoe type, controlling for other risk factors. Results: A majority of soldiers wore cushioning shoes (57%), followed by stability shoes (24%), MRS (17%), and motion control shoes (2%). Soldiers wearing MRS were slightly younger than those wearing TRS ( P < .01); performed more push-ups, sit-ups, and pull-ups ( P < .01); and ran faster during the 2-mile run ( P = .01). When other risk factors were controlled, there was no difference in injury risk for running shoe type between soldiers wearing MRS compared with TRS. Conclusions: Soldiers who chose to wear MRS were younger and had higher physical performance scores compared with soldiers wearing TRS. When these differences are controlled, use of MRS does not appear to be associated with higher or lower injury risk in this population.